ADVANTAGES AND DISADVANTAGES OF HOME-BASED REHABILITATION - Sodiqova Durdona Sultonmurodovna; Karimalieva Dildora Qodirjonovna; Ganieva Shoira A'zamovna (Web of Journals Publishing, 2025)
This article highlights the role, tasks, and principles of rehabilitation in restoring and strengthening health after illness, as well as the advantages and disadvantages of home-based rehabilitation.
Keywords: Rehabilitation, World Health Organization, therapy, autogenic training, medical diagnostics, functional diagnostics, psychodiagnostics.